Molar Incisor Hypomineralisation-To Extract or to Restore beyond the Optimal Age? - Mustafa Elhussein; Hasan Jamal (MDPI AG, 2020)
The management of compromised first permanent molars (FPMs) in children presents a clinical challenge to the dental team. Hypomineralised FPMs in molar incisor hypomineralisation (MIH) conditions could undergo post-eruptive breakdown, making them susceptible to caries, leading to their subsequent loss. The planned extraction of compromised FPMs is a valid alternative to complex restorative treatment. However, establishing the presence or absence of third permanent molars, amongst other considerations, is crucial to reaching a successful outcome. Clinicians should understand the importance of an orthodontic examination around the age of 8 years old with regard to establishing a differential therapeutic decision about the ideal timing of MIH-affected FPMs' extraction in children. The aim of this article is to highlight that, with an interdisciplinary approach, a good outcome can be achieved following the extraction of poorly prognosed FPMs. The most cost-effective way of addressing MIH-affected FPMs is extraction, followed by orthodontic space closure when indicated. This obviates the need for the repeated restorative replacement and saves perfectly healthy premolars from being extracted for space creation in orthodontic treatment in several clinical scenarios.